Mean platelet volume at baseline and immune thrombocytopenia relapse in Chinese newly-diagnosed patients: a retrospective cohort study. Issue 9 (21st October 2018) - Chen, Chi; Song, Jun; Wang, Qing; Wang, Lin-Hui; Guo, Peng-Xiang
ABSTRACT: Objective: In China, the ability of the current immune thrombocytopenia (ITP) guideline to stratify recurrent risk at diagnosis is limited. This study aimed to investigate whether mean platelet volume at diagnosis (MPV) is a risk factor for ITP relapse in Chinese. Methods: The present study was a retrospective cohort study. Two hundred thirty-three adult patients with newly diagnosed ITP were consecutively and nonselectively collected from March 2013 to June 2017. The exposure and outcome variable were MPV at baseline and relapse-free survival at 6 months. Other covariants included demographic data, general information, variables that can affect MPV reported by previous literature and risk factors of ITP relapse. Results: After adjusting potential confounders, the non-linear relationship was detected between MPV and ITP relapse, and inflection point was 21. The effect sizes and the confidence intervals on the left and right sides of inflection point were 1.30 (1.22–1.39) and 0.89 (0.76–1.04), respectively. Subgroup analysis showed, in subjects with hyperuricemia (1.54 (1.24, 1.90)), MPV showed significant differences from non-hyperuricemia (1.19 (1.13, 1.25)), and the p for interaction was less than 0.05. Conclusion: The relationship between MPV and ITP relapse is non-linear. MPV is an independent risk factor of ITP relapse when MPV is less than 21 fl.